The role of image intensifiers in minimally invasive cardiac surgery: A case report (Indian Journal of Case Reports, 2025)
Transesophageal echocardiography (TEE) is a critical tool in total coronary revascularization via anterior thoracotomy (TCRAT). It provides real-time imaging that enhances intraoperative decision-making. However, it can be a problem in patients with prior esophageal surgery. This case report explores the successful use of image intensifiers in a 64-year-old male patient who underwent TCRAT with prior esophageal surgery. Anatomical restrictions caused by the patient’s subtotal esophagectomy made TEE infeasible. A hybrid operating room facilitated guidewire and peripheral cannula placement using image intensifiers, providing critical real-time imaging and guidance. This case’s success illustrates the flexibility needed in sophisticated surgical settings as well as the incorporation of technology in cardiac surgery.